Jets with electrons from boosted top quarks - Suman Chatterjee; Rohini Godbole; Tuhin S. Roy (Journal of High Energy Physics)
Abstract We propose a method to identify jets consisting of all the visible remnants of a boosted top quark decaying semileptonically with an electron in the final state. An overlap of electron shower with the b quark initiated shower, and the large nontrivial energy-momentum carried by the invisible neutrino in the top quark decay are the two obstacles to achieving this aim. Our method uses the distribution of energy in different parts of the detector to identify a jet containing an energetic electron, involves use of substructure of the jet to determine the momentum associated with the electron and then completes the identification of top jet with the construction of new variables which would reflect the top quark decay kinematics. The last part involves an ansatz of the existence of a massless, invisible four-momentum roughly collimated with the electron, whose four- momentum when combined with that of the the electron and the full jet, reconstructs to the W boson and the top quark respectively. We demonstrate the efficacy of this proposal using simulated data and show that our method not only reduces the backgrounds from light flavor jets, b jets from QCD, and hadronic top jets, it can also tell apart jets rich in electrons but not due to top quark decays.